Hubungan Masa Kerja Dengan Kejadian Dermatitis Kontak Akibat Kerja Pada Cleaning Service Di Rumah Sakit Umum Cut Meutia Aceh Utara - Erida, Bela Nurfitri; Sawitri, Harvina; Mellaratna, Wizar Putri (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2024)
Occupational contact dermatitis is a skin condition caused by exposure to materials used at work. Cleaning service is a person who is in charge of maintaining cleanliness and providing cleaning services that have the potential to experience occupational contact dermatitis. The purpose of this study was to the relationship between years of service with the incidence of occupational contact dermatitis in the cleaning service workers at the cut meutia general hospital, north aceh. The research method used is observational analytic through a cross sectional approach. Sampling in this study used a consecutive sampling technique of 84 people who met the inclusion and exclusion criteria. The measuring instrument used is the NOSQ 2002-LONG questionnaire and the diagnosis is confirmed by the mathias criteria. Analysis of the data from this study used a statistical test in the form of a chi-square test. The results of this study found that most of the respondents were women and adults. Most of the cleaning services at the Cut Meutia Aceh Utara General Hospital have a working period of >2 years (79.8%). Cleaning service at the Cut Meutia General Hospital, North Aceh who experienced contact dermatitis due to work as many as 45 people (53.6%). The conclusion is that there is no significant relationship between years of service with the incidence of occupational contact dermatitis in the cleaning service workers at the cut meutia general hospital, north aceh. with a p value of 0.448 (p > 0.05).